Rotatable Response Surface Designs for S1^n1 x S2^n2 Incorporating Neighbour Effects - Ashutosh Dalal; Seema Jaggi; Eldho Varghese; Arpan Bhowmik; Cini Varghese; Anindita Datta (Revstat Statistical Journal)
This paper describes the response surface methodology for mixed-level factors of the form S1n1 x S2n2 when experimental units are affected by the adjacent neighbouring units. Conditions have been derived for the orthogonal estimation of the parameters of the model. A method of construction has been developed and the developed designs satisfy the rotatability conditions. Some particular cases of S1n1 x S2n2 are described. An R package named rsdNE developed for the generation of these designs has also been discussed.